2014
DOI: 10.1051/epjconf/20146603095
|View full text |Cite
|
Sign up to set email alerts
|

New candidate for deformed halo nucleus in Mg isotopes through analysis of reaction cross sections

Abstract: Abstract. The total reaction cross sections of Mg isotopes on a 12 C target at 240 MeV/nucleon have been analyzed with a fully microscopic framework, i.e., the double folding model with the density calculated by antisymmetrized molecular dynamics. Our results well reproduce the latest experimental data except 37 Mg as a new candidate for a deformed halo nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this study, they have observed large reaction cross section value for 37 Mg as compared to other isotopic chain and consequently predicted 37 Mg to have a halo structure. In another study S. Watanabe [11] concluded from their fully microscopic double folding frame work with the AMD densities, that 37 Mg exhibits deformed halo structure. In our earlier work we explored the structure of some isotopes of Ne, Mg and Si [12].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, they have observed large reaction cross section value for 37 Mg as compared to other isotopic chain and consequently predicted 37 Mg to have a halo structure. In another study S. Watanabe [11] concluded from their fully microscopic double folding frame work with the AMD densities, that 37 Mg exhibits deformed halo structure. In our earlier work we explored the structure of some isotopes of Ne, Mg and Si [12].…”
Section: Introductionmentioning
confidence: 97%
“…The halo structure originates due to extremely weak bound nucleons which decouple from the nuclear core. The interaction cross sections of such nuclei like 6,8 He, 11 Li and 11,14 Be [1] are anomalously high due to large magnitude of consolidated root mean square (rms) radii. The one neutron/proton breakup of halo projectiles with stable target at near/far barrier energies is one of the tool to investigate the structure of such systems [2].…”
Section: Introductionmentioning
confidence: 99%